Simulation of specimen-induced aberrations for objects with spherical and cylindrical symmetry. - Schwertner, M; Booth, M; Wilson, T (2004)
Wavefront aberrations caused by the refractive index structure of the specimen are known to compromise signal intensity and three-dimensional resolution in confocal and multiphoton microscopy. However, adaptive optics can measure and correct specimen-induced aberrations. For the design of an adaptive optics system, information on the type and amount of the aberration is required. We have previously described an interferometric set-up capable of measuring specimen-induced aberrations and a method for the extraction of the Zernike mode content. In this paper we have modelled specimen-induced aberrations caused by spherical and cylindrical objects using a ray tracing method. The Zernike mode content of the wavefronts was then extracted from the simulated wavefronts and compared with experimental results. Aberrations for a simple model of an oocyte cell consisting of two spherical regions and for a model of a well-characterized optical fibre are calculated. This simple model gave Zernike mode data that are in good agreement with experimental results.